Treatment of perianal fistulas in Crohn’s disease - review of literature and current recommendations - Szawica, Dominik; Kuźniar, Aleksandra; Fularska, Kamila; Oleszko, Michał; Wąsiewicz, Edward; Bernacki, Radosław; Bernacki, Piotr; Dutka, Martyna; Zardzewiały, Witold (Quality in Sport, 2023)
Introduction: Crohn's disease is an idiopathic inflammatory disorder of unknown etiology, associated with genetic, immunological, and environmental factors. The incidence of this disease continues to rise in developed countries. In almost 25% of patients, perianal fistulas occur during the course of the disease, which are difficult to treat and significantly impair the patient's quality of life. Aim of the study: To summarize the current state of knowledge on the treatment of Crohn's disease with perianal fistulas, with a particular focus on biological therapies and stem cell treatments. Methods and Materials: A systemic review was conducted using PubMed, Google Scholar, and ScienceDirect databases and it was limited to studies published in last 5 years. The search strategy was based on following terms: "Crohn's disease", "perianal fistula", "biological treatment", and "inflammatory bowel disease". Results: In recent years, there has been intensive research into new treatment options for perianal fistulas in Crohn's disease. Infliximab remains the first-line therapy, best controlled by monitoring the drug concentration in the serum. Alternatively, other drugs such as ustekinumab and vedolizumab may be considered. The combination of biological and surgical treatment is a recognized standard of care and modern, minimally invasive techniques that preserve sphincters, such as the FiLaC™ laser procedure, are increasingly being used. A novel and very promising therapeutic approach is based on mesenchymal stem cells, which may offer hope for patients who do not improve with standard treatment. Conclusion: Perianal disease in patients with Crohn's disease poses a significant therapeutic challenge and has a substantial negative impact on the physical and emotional well-being of patients. Despite the existence of various therapeutic options, a certain percentage of patients still fails to achieve clinical remission. Further research into new therapies is necessary.